The use of video reflection to enhance EFL pre-service teachers’ teaching practice during practicum - Kwangsawad, Thooptong (Asian Journal of Interdisciplinary Research, 2021)
This paper reports on the use of video reflection to enhance EFL pre-service teachers’ teaching practice during their practicum period. This study also reports on the participants’ experiences, reactions, and perceptions towards the use of video recordings of their teaching practice. Eighty-four EFL pre-service teachers participated in the study with written reflections on the videos of their own teaching comprising the data analyzed in the study. The results revealed that using video reflection helped the participants improve their teaching. Furthermore, the participants expressed a strong belief in the value and effectiveness of viewing videos of their own and peer teaching lessons and receiving feedback from the supervisor monthly as to reach realizations and changes about their teaching practice in the practicum. The implication of the study suggests ways to better connect university courses with the actual classroom practices to provide EFL pre-service teachers the maximum support to practicalize their knowledge during the practicum.